2022
DOI: 10.1177/0192513x221106736
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Nothing Serious I Suppose’ Family Help-Seeking for Adolescent Social Anxiety

Abstract: This article investigates how families seek professional supports for adolescent social anxiety. Many adolescents meet diagnostic criteria for social anxiety disorder but do not access professional mental health supports. Access to timely interventions is important because social anxiety has a range of developmental implications and typically persists into adulthood when untreated. Twelve adolescents (aged 14 to 18) who had attended mental health services for support with social anxiety and 13 mothers of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…For many parents in our study, their ability to seek and obtain care was hindered by not knowing when to seek help and where to access services, having to learn to navigate the mental heath care system, facing healthcare professionals’ dismissal of their concerns and knowledge, and having limited financial resources to obtain services in the private sector or those not covered by insurance plans. Our findings are consistent with: (1) results of the handful of studies that have documented parents’ lived experience of access to mental health services for child anxiety disorders both in Canada [ 44 , 45 ] and abroad [ 12 , 41 , 42 ]; (2) the few studies that have examined barriers to access in the context of child anxiety disorders [ 38 42 ]; and (3) the literature on the barriers parents face when accessing mental health services (not specific to anxiety) for their child [ 30 36 ]. The finding that the barriers related to parents’ ability to obtain care identified in this study have been reported in other studies as noted above highlights the need to support parents, regardless of mental health condition for which care is sought, by strengthening their ability to identify mental health problems and ensuring information about available services and mental health care system navigation is readily available (e.g., primary care clinics).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…For many parents in our study, their ability to seek and obtain care was hindered by not knowing when to seek help and where to access services, having to learn to navigate the mental heath care system, facing healthcare professionals’ dismissal of their concerns and knowledge, and having limited financial resources to obtain services in the private sector or those not covered by insurance plans. Our findings are consistent with: (1) results of the handful of studies that have documented parents’ lived experience of access to mental health services for child anxiety disorders both in Canada [ 44 , 45 ] and abroad [ 12 , 41 , 42 ]; (2) the few studies that have examined barriers to access in the context of child anxiety disorders [ 38 42 ]; and (3) the literature on the barriers parents face when accessing mental health services (not specific to anxiety) for their child [ 30 36 ]. The finding that the barriers related to parents’ ability to obtain care identified in this study have been reported in other studies as noted above highlights the need to support parents, regardless of mental health condition for which care is sought, by strengthening their ability to identify mental health problems and ensuring information about available services and mental health care system navigation is readily available (e.g., primary care clinics).…”
Section: Discussionsupporting
confidence: 90%
“…The poor availability of services was also a common theme in our study as was lack of timely services and interim supports. These findings are consistent with results of qualitative studies that have examined parents’ lived experience of access in the context of child anxiety disorders [ 12 , 41 , 42 , 44 , 45 ], studies that have focused specifically on access to services for childhood anxiety [ 38 40 ], and the larger body of evidence on barriers parents face when accessing mental health services for their child (non-specific to anxiety or a mental health diagnosis) [ 30 36 ]. Our findings thus reinforce that for childhood anxiety as well as other childhood mental health disorders, service availability (whether services are physically available and can be reached in a timely manner) [ 26 ] necessitates ongoing investment and enhancement.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations